The German Generals Talk - Liddell Hart, B. H., 1895-1970 (Rawalpindi, Pakistan Army Education Press, 1975)
Statements made to the author in 1945 by German generals detained as prisoners of war with the author's comments.
Include Index and Maps
Keywords: Germany -- World War (1939-1945) -- Military campaigns